The Link between HR Attributions and Employees’ Turnover Intentions - Juliana Caesaria Tandung (Gadjah Mada International Journal of Business, 2016)
Human Resources Management (HRM) is part of the organizational functions that contribute to the effectiveness of a firm’s performance, and brings an organization a competitive advantage through the implementation of its Human Resources (HR) practices. HR practices adopted by management are perceived or attributed subjectively by individual employees, and can in turn affect the employees’ attitudes and behavior (e.g. Job satisfaction and turnover intention). The purpose of this study is to contribute to the process-based approach by investigating the effect of HR attributions on turnover intentions, with job satisfaction playing a mediating role. The analysis is on the individual level, with 454 respondents from various organizations within the Netherlands. The results show that HR attributions can affect the turnover intention, through the presence of job satisfaction. Thus, it can be said that it is important to always consider the employees’ attitudes and behavior when examining their perception of HR practices, and in predicting their intention to leave.